A study on awareness of sexual harassment in the workplace among the employees of Sabah Railway Station Department / Norafidah Awang... [et al.] - Awang, Norafidah; Mohd Ali, Noor Hanizah; Yakinol, Yanadiana (2011)
Sexual harassment is not a new issue in Malaysia. Sexual harassment can be happen to anybody. Sexual harassment at workplace is an unwelcome or uninvited behavior of sexual nature, which is offensive, embarrassing, intimidating and affects an employee’s work performance, health and career or livelihood (Sabitha, M, 2008). Sexual harassment also can be defined as an unlawful to harass a person (an applicant or employee) because of that person’s sex. Harassment can include “sexual harassment” or unwelcome sexual advances, requests for sexual favors, and other verbal or physical harassment of a sexual nature (Equal Employment Opportunity Commission (EEOC), 1965). Nowadays, the problems regarding the sexual harassment is occurs rapidly as so many cases happen and some of it resulting the rapped cases. Furthermore, the sexual harassment is not taken seriously in Malaysia (Ivy Josiah, 2010). Thus, there are so many past researches in order to know the effects and the factors on the sexual harassment.